Rights Of Inheriting For Second Group (Case Study Karanganyar Religious Court) - Erlina Citra Widiastuti; Eka Damayanti (Jurnal Akta, 2019)
Basically inheritance is a movement of all the rights and obligations of a deceased person to his heirs. The notion of inheritance law is the law governing the transition of wealth which the person who died and the consequences for the heirsHeir rights arise before the opening of the inheritance in the sense that the beneficiary dies before the right to express their will in a testament / will. Heir ispeople for reasons (heredity, marriage/ Slavery) are entitled to part of the estate of the person who die.The second group includes beneficiariesThis group consists of the .People parents (father and / or mother) of the heir and brother and his descendants until the degree to 6. The problem of this study is how to apply the practice of the beneficiary to beneficiary groups both in the religious court Karanganyar, how legal considerations practices verdict heir for the second group wais expert in religious courts karanganyar and what challenges and solutions in implementing the decision of the heirs inherit rights groups both in the religious court karanganyar. As for the research method used is sociological, the source of the data used is primary data and data secondary obtained from the test site and library resources and documentation are collected through the identification and inventory of legislation, then the data were analyzed with qualitative methods .Based normative research and discussion concluded Setting Harso Suwito Kiman bin Marto Setiko had died, set Heirs Heirs and Successors Harso Suwito Kiman bin Marto Setiko As follows Supadmi, Rukiman, Darmi, Sutinem . Stated ¼ because the child had been cared for and maintain the adoptive parents to death, declare the contents of the letter made by Sri Mulyani and WR on 28 June 2006 are not enforceable by law actual fact, the decision legal considerations Considering that the disputed land the land that formerly came from the estate of his father gono pusoko  Considering that the plaintiff as legal heirs, that the transition process disputed land controlled by the Defendants unlawful and not based on law, Considering that based on the facts turned out to conference proceedings are not based on rights, obstruction is that plaintiff demanded that declared the legitimate heirs of Alm.Harso Suwito Kiman and reserves receive all property penin ggalan therefore -sertifikat certificate of land disputes in the matter otherwise lawful aquao but Alm.Harso Suwito Kiman had no biological children but has one adopted son named Sri Mulyani, and on 30 June 2006 stating that Supadmi and Sri Mulyani is the rightful heir, and the solution is Sri Mulyani get Supadmi ¼ and his wife get. Keywords: Rights of Inheriting; Heirs; Heirs of The Second Group.